Design and performance analysis of a novel switched ftth access network - Lau, Peng Wah (2002)
Over these years, rapid development of bandwidth consuming applications has pushed the existing network infrastructure to the limit particularly in the access layer. There has been many development of high speed protocols to meet the demands but the existing physical medium, which consists of copper-based network, do not have the capabilities to support these protocols. Thus, the problem still exist and as time goes by, more and more demand and the use of high bandwidth applications have really clogged the access line. This problem is referred to as the access network bottleneck problem. In addressing the access network bottleneck problem, Fiber-To-The-Home (FTTH) technology has been introduced in the local loop, taking advantage of optical fibers huge bandwidth. However, there is still one obstacle, which has been generally overlooked, which is, providing protection to the access line. The fiber optics access mainly consists of a single fiber running upstream and a single fiber running downstream. If a protection path were to be created, the network provider would have to lay another 2 fibers on the network. This would increase deployment costs and also costs for the subscribers. Thus, a new way of providing fault tolerance to the system has to be introduced, by taking costs consideration and also efficiency in deploying the solution. In this thesis, a novel scheme for providing fault tolerance to the FTTH system is introduced. Also, various classes of traffic are defined. All these classes of traffics can logically represent different applications based on their Quality of Service (QoS) requirements. These traffics are run on the switched FTTH access network model . The survival of the network is studied by terminating the supporting OLT unit one after another and observing the packet delay, packet loss ratio, the buffer occupancy and also the throughput of the switch. Results show that for different traffic classes, the number of supportable ONUs can exceed the standard value of the FSAN recommendations, which are 32 units per OLT. For example, for a two OLT access network, the maximum recommended supportable ONU units are 64 units whereas in the proposed system, up to a maximum of 128 ONU units can be supported under normal conditions; where there are no OLT failures or fiber breaks.